A Brief Review of Beneficial Effects of Yoga on Physical and Mental Health: Yoga on Physical & Mental Health - Syed, Sadat Ali; Akram, Muhammad; Rashid, Abid; Khalil, Muhammad Talha; Anwar, Hina; Laila, Umme; Zainab, Rida; Mohiuddin, Ghulam (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Yoga is focussed as an essential form of spiritual discipline based on an extremely subtle science bringing harmony between mind and body. It is an art and science of healthy living consisting largely of asanas. It is found to be one of the best exercises for physical and mental health. There is more need of supportive therapy for maintaining physical and mental health apart from current treatment by different forms of medicine. It is known to relax body, promote immunity and thereby prevent illness seeing as effective, acceptable and cost-effective for body and mind to relieve stress. An online search for studies done using medline terms like yoga, physical health & mental health were done. The studies have shown that it improves physical illness and promotes mental calmness by removal of anxiety, depression & stress thereby excel the treatment of diseases. These gives positive change such as well-being and happiness to the individual and increase the quality life years.